Carboxysome Mispositioning Alters Growth, Morphology, and Rubisco Level of the Cyanobacterium Synechococcus elongatus PCC 7942 - Rees Rillema (American Society for Microbiology, 2021)
ABSTRACT Cyanobacteria are the prokaryotic group of phytoplankton responsible for a significant fraction of global CO2 fixation. Like plants, cyanobacteria use the enzyme ribulose 1,5-bisphosphate carboxylase/oxidase (Rubisco) to fix CO2 into organic carbon molecules via the Calvin-Benson-Bassham cycle. Unlike plants, cyanobacteria evolved a carbon-concentrating organelle called the carboxysome—a proteinaceous compartment that encapsulates and concentrates Rubisco along with its CO2 substrate. In the rod-shaped cyanobacterium Synechococcus elongatus PCC 7942, we recently identified the McdAB system responsible for uniformly distributing carboxysomes along the cell length. It remains unknown what role carboxysome positioning plays with respect to cellular physiology. Here, we show that a failure to distribute carboxysomes leads to slower cell growth, cell elongation, asymmetric cell division, and elevated levels of cellular Rubisco. Unexpectedly, we also report that even wild-type S. elongatus undergoes cell elongation and asymmetric cell division when grown at the cool, but environmentally relevant, growth temperature of 20°C or when switched from a high- to ambient-CO2 environment. The findings suggest that carboxysome positioning by the McdAB system functions to maintain the carbon fixation efficiency of Rubisco by preventing carboxysome aggregation, which is particularly important under growth conditions where rod-shaped cyanobacteria adopt a filamentous morphology. IMPORTANCE Photosynthetic cyanobacteria are responsible for almost half of global CO2 fixation. Due to eutrophication, rising temperatures, and increasing atmospheric CO2 concentrations, cyanobacteria have gained notoriety for their ability to form massive blooms in both freshwater and marine ecosystems across the globe. Like plants, cyanobacteria use the most abundant enzyme on Earth, Rubisco, to provide the sole source of organic carbon required for its photosynthetic growth. Unlike plants, cyanobacteria have evolved a carbon-concentrating organelle called the carboxysome that encapsulates and concentrates Rubisco with its CO2 substrate to significantly increase carbon fixation efficiency and cell growth. We recently identified the positioning system that distributes carboxysomes in cyanobacteria. However, the physiological consequence of carboxysome mispositioning in the absence of this distribution system remains unknown. Here, we find that carboxysome mispositioning triggers changes in cell growth and morphology as well as elevated levels of cellular Rubisco.